What the Victorians Got Wrong. - Yorke, Stan (Countryside Books, 2013)
The nineteenth century was an era of scientific advance like no other in history. Railways were built, bridges constructed, rivers tamed and electricity harnessed, to the great benefit of all. But progress was only achieved at high cost. Impatience for achievement too often resulted in catastrophe and disaster. These accounts of how the Victorians stumbled into appalling errors of judgement offer a sobering counter balance to the often related tales of glorious successes.